Antimicrobial efficacy of intracanal and extracanal heated sodium hypochlorite against Enterococcus faecalis: An in vitro study - Vishnu Rathore; Deepali Samel; Prashant Moogi; Siddhesh Bandekar; Shirin Kshirsagar; Chinmay Vyas (Wolters Kluwer Medknow Publications, 2020)
Introduction: Enterococcus faecalis is the most common bacterial species in persistent root canal infections. Sodium hypochlorite (NaOCl) has shown antibacterial activity against E. faecalis at room temperature. It has been proven that heating enhances the properties of NaOCl. Thus, the aim of the present study is to compare the effectiveness of intracanal and extracanal heated NaOCl against E. faecalis. Methodology: The specimens were decoronated up to cementoenamel junction and prepared up to size F3 and were inoculated with E. faecalis. Then, teeth were divided into four groups and irrigation was performed. Group A - 5% NaOCl (Prime Dental Products Pvt. Ltd., India) at room temperature, Group B - 5% NaOCl (Prime Dental Products Pvt. Ltd., India) heated extracanal at 600C in a water bath, Group C - 5% NaOCl (Prime Dental Products Pvt. Ltd., India) intracanal heated using 980 Nm diode laser, and Group D - 5% NaOCl (Prime Dental Products Pvt. Ltd., India) intracanal heated using Elements System-B. The antimicrobial efficacy was tested by collecting transfer fluid and counting the colony forming units of viable E. faecalis on agar plates. Results: Following the disinfection protocol significant reduction in E. faecalis count was seen in the groups irrigated using intracanal heated and extracanal heated NaOCl with that of NaOCl used at room temperature with a significant value of P ≤ 0.001*. Conclusion: Within the limitations of the present study, it can be concluded that intracanal heating using Elements System-B Heat Source and Diode Laser has better antimicrobial efficacy as compared to that of NaOCl extracanal heated and at room temperature.